Challenges of economic development GAP: A case study in selected rural villages at Beaufort, Sabah - Wong, Sing Yun; Jain Yassin (National Institute of Public Administration (INTAN) Bukit Kiara, 2023)
Globally, governments prioritise economic development, with the pursuit of balanced growth and prosperity as the main objective. There is, however, a substantial divide between those areas that are economically thriving and those that are lagging in many states and regions. Malaysia is not exceptional in experiencing the problem of a development gap. The development disparities between urban and rural areas remain unresolved and inequalities issues persist. The main objective of this article was to delve into the example of economic and development issues in the rural areas within the state by drawing inferences based on a case study in the Parliament Constituency of Beaufort, Sabah. This research conducted in the Parliament Constituency of Beaufort, Sabah was part of the issue-mapping research done by the All-Party Parliamentary Group on Sustainable Development Goals (APPGM-SDG) to identify the most pressing development issues faced by the locals. By employing a Focus Discussion Group (FGD), valuable in-depth insights can be gathered on the current socioeconomic development situations in these remote villages and the social inequalities faced by the villagers. The findings from this research highlighted some of the critical issues faced by the local communities which comprised of poor infrastructure development, communities struggling economically with limited economic activities available, and depressing environmental problems. Drawing on these findings will allow policymakers, researchers, and practitioners to be able to address better the current regional imbalances through new strategies devised that can resolve these root causes.